UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PERSAMAAN KUADRAT MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) - Sri Hartuti (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
This study aims to describe the level of mathematics learning outcomes of students in Class IXC SMP Negeri 1 Tempuran after the implementation of Cooperative Learning Model Type Numbered Heads Together (NHT). This research is class action research (PTK). Each cycle consists of three stages of activities, namely planning, action implementation and observation, and reflection. The subjects of this study were students of class IXC SMPN 1 Tempuran Magelang Regency with a total of 32 students. Data collection in this study used teacher and student activity observation sheets and written tests. Data analysis techniques used were descriptive qualitative and descriptive quantitative with percentages. The results showed an increase in Mathematics learning outcomes of Quadratic Equation material in class IXC SMP Negeri 1 Tempuran students after the implementation of learning with the NHT type cooperative learning model in cycle I on average was 74.88 after cycle II on average was 83.03. Behavioral changes that occurred in students of class IXC SMP Negeri 1 Tempuran in the implementation of learning with the NHT type cooperative model to improve learning outcomes of Mathematics Quadratic Equation material include the following 1) students are more disciplined by showing orderly behavior and obeying the rules applied during learning, 2) students have high curiosity about the problems given, 3) students have high responsibility for the tasks given, 4) students are better able to cooperate with their friends, 5) students are more confident in their own ability to carry out activities or actions, 6) students are more honest and trustworthy in words, actions and work.